1984
DOI: 10.1021/jm00367a009
|View full text |Cite
|
Sign up to set email alerts
|

8-Hydroxy-2-(alkylamino)tetralins and related compounds as central 5-hydroxytryptamine receptor agonists

Abstract: A series of 2-(alkylamino)tetralins related to 8-hydroxy-2-(di-n-propylamino)tetralin (21) were prepared and tested as dopamine (DA) and 5-hydroxytryptamine (5-HT) receptor agonists. Several of the compounds were potent 5-HT agonists devoid of DA-mimetic effects. N-Ethyl or N-propyl substitution of 8-hydroxy-2-aminotetralin gave the most potent agonists. It was shown that the most potent compound, (+)-21, has the 2R configuration. 5,8-Di-methoxy-2-(di-n-propylamino)tetralin (31) was found to be a weak DA agoni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 10 publications
3
33
0
Order By: Relevance
“…At the 5-HT 1A receptor site the R-enantiomers regularly show the higher affinity. As expected from the results of the structure activity relationships of the 2-aminotetralins [28] , the optimum is obtained with the di-n-propylamino substitution. The pK I values for the donor-type (-OH, -OCH 3 , -OC 3 H 7 ) substituted tertiary compounds are higher than those for the acceptor-type (-CONH 2 , -CN, -CONHCH 2 C 6 H 11 ) substituted ones.…”
Section: Ss′-(+)-7-nbenzylcarbamoyl-l-(1-phenylethylamino)indan Hysupporting
confidence: 67%
See 3 more Smart Citations
“…At the 5-HT 1A receptor site the R-enantiomers regularly show the higher affinity. As expected from the results of the structure activity relationships of the 2-aminotetralins [28] , the optimum is obtained with the di-n-propylamino substitution. The pK I values for the donor-type (-OH, -OCH 3 , -OC 3 H 7 ) substituted tertiary compounds are higher than those for the acceptor-type (-CONH 2 , -CN, -CONHCH 2 C 6 H 11 ) substituted ones.…”
Section: Ss′-(+)-7-nbenzylcarbamoyl-l-(1-phenylethylamino)indan Hysupporting
confidence: 67%
“…A possible explanation for this exception is the great three-dimensional extension of the acceptor substituent. Arvidsson et al [28] have already shown that the orientation at the receptor depends on the aromatic substitution pattern. The R-(-)-7-propoxy-1-(din-propylamino)indan hydrochloride (R-(-)-30) ( pK I = 7.07±0.19) has the highest affinity of all tested compounds, but is about 45 times less active than the reference compound 8-OH-DPAT (36) (pK I = 8.70) ( Table 7).…”
Section: Ss′-(+)-7-nbenzylcarbamoyl-l-(1-phenylethylamino)indan Hymentioning
confidence: 97%
See 2 more Smart Citations
“…Introduction 8-Hydroxy-2-(di-n-propylamin)tetralin (8-OH-DPAT), the prototypical 5-HT 1A receptor agonist (Arvidsson et al, 1981(Arvidsson et al, , 1984, has been widely used as a radioactive ligand to study the distribution of 5-HT 1A receptors (Gozlan et al, 1983) and to induce various physiological and behavioural responses in the rat (Hjorth, 1985;Tricklebank et al, 1985). The R-and S-enantiomers of 8-OH-DPAT have similar binding affinities to the 5-HT 1A receptors in the rat hippocampus (Cornfield et al, 1991;Foreman et al, 1995) and to the cloned h5-HT 1A receptors (Lejeune et al, 1997).…”
mentioning
confidence: 99%